Emotional intelligence and coping styles stress at of single mothers - Terelak, Jan Felicjan; Jasiura, Małgorzata (Studia Psychologica: Theoria et praxis, 2012)
Work mum empirical character and a roll of the emotional intelligence is regarding the moderating evaluation in the selection of the coping style stress of the single mothers. With theoretical base of the work joke “ability” of the Mayer’s and Soloveys Model Emotional Intelligence and the Endler’s and Parker,s concept of coping styles stress. In examinations 27 single mothers took part in the century 21-41 years old, disabled professionally, inhabiting Houses of Single Mothers and 40 mothers in the century 2640 years old, retreats of professionally active. To do the description of the intelligence an Test Emotional Intelligence (TIE) was used and to do evaluations of coping styles stress - Coping Inventory for Stressful Situations (CISS). They stated among others that professionally active single mothers more often used the sentence of coping styles stress, single mothers using the welfare much more often concentrate on the emotional and avoidance style.